iFUTURE@UMPSA gathers young leadership talents at global level - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
GAMBANG, 19 June 2025 – The iFUTURE@UMPSA programme took place in full splendour at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Gambang Campus, bringing together various parties, including students, lecturers, agencies, and industries, in driving the nation’s future talent development agenda.